McVicar, Kate - Kealey, Gregory S. (Dictionary of Canadian Biography, 1982)
McVICAR, KATE (Katie), shoe worker and union leader; b. c. 1856 at Hamilton, Canada West; d. there 18 June 1886. Katie McVicar, daughter of a poor Scottish tinsmith and his English-born wife, joined two older sisters in the Hamilton labour force in the early 1870s. Like most women who went into factory work in the late 19th century, she began as a single woman, living at home, in order to augment her family’s income. However, unlike most, she remained single and continued to live at home until her early death at the age of 30. Her comparative longevity as a factory operative accounts to some degree for her emergence as a prominent leader in the Knights of Labor. –Introduction

Canada's Age of Industry, 1849-1896 - Cross, Michael S.; Kealey, Gregory S. (McClelland and Stewart, 1982)
...This volume presents a series of scholarly articles which range from an essay by Gregory Kealey on Toronto's Industrial Revolution in the last half of the nineteenth century to a fascinating study by Wendy Mitchener of the Women's Christian Temperance Union, "A Study of Nineteenth-Century Feminism." Also included are examinations of the working class, violence and protest, social structure and government encouragement of industrial development from 1849 to 1896. –Publisher's description
OCLC: 9277514
Keywords: Aufsatzsammlung; Canada; Canada Conditions sociales 1867-1918; Canada Conditions sociales 19e siècle; Canada Conditions sociales Jusqu'à 1763; Canada Conditions économiques 1763-1867; Canada Conditions économiques 1867-1918; Canada Conditions économiques 19e siècle; Canada Economic conditions 1763-1867; Canada Economic conditions 1867-1918; Canada Economic conditions 19th century; Canada Industrialisation Socioeconomic aspects 1841-1911; Canada Social conditions 1867-1918; Canada Social conditions 19th century; Canada Social conditions To 1763; Economic history; Geschichte 1849-1896; History; Industrie Canada Histoire 19e siècle; Industries; Industries Canada History 19th century; Kanada; Social conditions; Sozialgeschichte 1849-1896; To 1899; Wirtschaft

Dreaming of What Might Be: The Knights of Labor in Ontario, 1880-1900 - Kealey, Gregory S.; Palmer, Bryan D. (Cambridge University Press, 1982)
As Canada's most industrialised province, Ontario served as the regional centre of the Noble and Holy Order of the Knights of Labor, an organisation which embodied a late nineteenth-century working-class vision of an alternative to the developing industrial-capitalist society. The Order opposed the exploitation of labor, and cultivated working-class unity by providing an institutional and cultural rallying point for North American workers. By 1886 thousands of industrial workers had enrolled within the ranks of Ontario's local and district assemblies. This book examines the rise and fall of the Order, providing case studies of its experience in Toronto and Hamilton and chronicling its impact across the province. –Publisher's description
Google-Books-ID: y32w_mxffhEC
Keywords: Business & Economics / Labor / General; History / Europe / Renaissance

Editor's Note = Notes des directeurs [10, Fall/Automne 1982] - Kealey, Gregory S.; Palmer, Bryan D. (Labour / Le Travail, 1982)
Expresses appreciation to departing/arriving editorial board members, in particular Ross McCormack who also contributed in his capacity as President of the Canadian Committee on Labour History. Welcomes Bryan Palmer as review editor and Robert Babcock as incoming CCLH president. Takes note of two articles in the issue that were originally conference papers, the oral history project of Sudbury labour leader Jim Tester (his address is published in the issue), the bibliography compiled by Douglas Vaisey and Marcel Leduc, and the report of recent archival acquisitions by Danny Moore.

The Poor in Winter: Seasonality and Society in Pre-Industrial Canada - Fingard, Judith (Pre-Industrial Canada, 1760-1849, 1982)
This volume presents a selection of scholarly articles designed to introduce the student to the currents of social change and development in Canada from 1760 to 1849. With contributions by such respected academic writers as Harold Adams Innis, Judith Fingard, and Sylvia Van Kirk, it provides valuable insights into the role of the working class, violence and protest, class conflicts, and the economic structure of a newly developing nation. –Publisher's description on book cover